Climate change adaptation and economic profitability: crop land shifting to mango orchard in Rajshahi region (Bangladesh Rice Journal, 2015)
Barind ecosystem (Rajshahi Region) is unfavourable for field crop production but suitable for production of fruits like mango, litchi and jujube etc. Thus, an investigation was made to find out the causes, challenges and opportunity of crop land shift to mango orchard in Barind areas. A total of 85 mango growing farmers were randomly selected for interviewing. The dominant mango orchard based patterns are: i) Wheat-Fallow-T. Aman (30%); and ii) Mustard-Fallow-T. Amam (29%). About 75% farmers are transforming crop land into mango orchard because of water scarcity, high profitability, easy cultivation process, land suitability and favourable environment for mango cultivation. Mango farmers obtained on average 231 kg/ha yield in 1st quarter (year 1-3) and then production increased sharply and reached 2,190 kg/ha in 5th quarter (year 13-15). The highest gross return of mango was found in the 5th quarter. The estimated net present worth (NPW) of the project was Tk 99,588 per hectare, which indicates that mango cultivation was profitable in Rajshahi area. The internal rate of return (IRR) was 28%, which is higher than the opportunity cost of capital. However, increasing life span of mango orchard increases yield loss of both rice and non-rice crops. In 11-year-old mango orchard, intercrop yield reduced drastically (65%). More than 83% farmers obtained increased income and about 67% achieved better livelihoods due to mango cultivation. However, there is a possibility to decrease food grain, pulses, oil seed and vegetable production in the long run. Therefore, planned mango cultivation is needed along with ensured credit facilities through both institutional and non-institutional sources for mango cultivation, preservation and marketing.Bangladesh Rice j. 2014, 18(1&2): 8-17